Analysis of Changes in the Glomerular Filtration Rate as Measured by the Cockroft-Gault Formula in the Early Period after Percutaneous Nephrolithotomy - Bayrak, Omer (The Korean Urological Association, 2012)
PURPOSE: We aimed to analyze the changes in kidney function during the postoperative early period caused by the application of percutaneous nephrolithotomy (PNL), which is commonly used in kidney stone surgery. MATERIALS AND METHODS: PNL was performed in 80 patients (48 men, 32 women) with kidney stones. The mean age of the patients was 43.71 years (range, 18 to 71 years). Preoperative and postoperative values for stone size, glomerular filtration rate (GFR), serum creatinine, urea, electrolytes (Na, K, Cl), and Hb were compared in 80 patients in whom PNL surgery was performed. The formula of Cockroft-Gault was used to calculate the GFR during the early postoperative period (72 to 96 hours). RESULTS: Statistically significant decreases after PNL were observed in average stone size (preoperative, 627.75±375.10 mm(2); postoperative, 81.70±16.15 mm(2)), serum urea (preoperative, 38.40±17.26 mg/dl; postoperative, 33.28±16.98 mg/dl), and creatinine (preoperative, 1.03±0.53 mg/dl; postoperative, 0.97±0.55 mg/dl) and an increase was observed in GFR (preoperative, 104.30±37.30 ml/min; postoperative, 112.38±40.1 ml/min). No changes were detected in the serum electrolyte values (Na, K, Cl). Multiple access, operation time, and type of lithotripter did not have any significant effects on the change in the GFR. CONCLUSIONS: In light of our results, PNL for kidney stone operations appears to be a reliable and efficient method that provides recovery of kidney functions in the early post-operative period by increasing the GFR and with high stone-free rates.